2016
DOI: 10.1007/s10439-016-1624-4
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Ablation by a Synergistic Combination of Electroporation and Electrolysis Delivered by a Single Pulse

Abstract: A synergistic combination of electroporation and electrolysis (SEE) has been found with distinct advantages over tissue ablation by electrolysis or electroporation alone. Minimally invasive tissue ablation by electrolysis uses a low magnitude direct electric current to produce a lesion due to the creation of chemical products that result in cell death. Electroporation creates permeabilizations in the cell membrane which may lead to loss of cell homeostasis and cell death. When these two modes of tissue ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Mechanistic understanding of the cell death induced by electrolytic ablation is required to enable its further development for widespread clinical application. Furthermore, understanding cellular changes induced by electrolytic ablation will enhance parameter selection for related electrochemical therapies, including IRE, electrochemotherapy, and gene electrotransfer, which may have synergistic effects when combined with electrolytic ablation 39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic understanding of the cell death induced by electrolytic ablation is required to enable its further development for widespread clinical application. Furthermore, understanding cellular changes induced by electrolytic ablation will enhance parameter selection for related electrochemical therapies, including IRE, electrochemotherapy, and gene electrotransfer, which may have synergistic effects when combined with electrolytic ablation 39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary, acute study, in a small rodent animal model, has demonstrated the feasibility of tissue ablation with EDW. The results have shown that a very short, single millisecond EDW can ablate large volumes of tissue without attendant muscle contraction (12). We found that the EDW pulse combines the advantages of electrolytic ablation, reversible electroporation and irreversible electroporation, without the disadvantages.…”
Section: Introduction Introductionmentioning
confidence: 78%
“…For the analyzed lesion (lesion no 6), induced on the diaphragmatic surface of the medial left lobe, this was followed by an exponential decay wave form with the following parameters: peak voltage 960V, capacitance charge -122 pulse time constant 97 ms. The parameters chosen for this study were drawn from the experimental results of (15).…”
Section: Results and Discussion Results And Discussionmentioning
confidence: 99%
“…In several recent papers we have shown that combining electroporation and electrolysis (E2) sagaciously yields a new technology of tissue ablation with certain advantages over tissue ablation by electroporation (reversible or irreversible) or electrolysis alone (Phillips et al, 2015; Phillips et al, 2016; Stehling et al, 2016). We have developed several possible synergistic electroporation and electrolysis (E2) protocols.…”
Section: Introductionmentioning
confidence: 99%